Environmental orientation and green competitive advantage of hospitality firms in South Africa: Mediating effect of green innovation - Olawale Fatoki (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The hospitality industry exerts significant pressure on the environment through the consumption of resources such as energy and water. However, the industry can also enhance environmental preservation through their operation and strategy. This study examined whether environmental orientation (internal and external) and green competitive advantage are significantly positively related. This study also investigated the indirect effect of green innovation. A quantitative research method was used for this study. The cross-sectional survey method was used as the method of data collection. This study used Partial Least Square Structural Equation modelling to test the hypotheses. The findings showed that environmental orientation and green competitive advantage are significantly positively related. The indirect effect of green innovation is significant. Theoretically, the study developed a model that linked green innovation to environmental orientation. Practically, the study suggests some recommendations on how the managers of hospitality firms can improve environmental orientation. These include the provision of training and development workshops on environmental strategy for management and employees.
Keywords: 650; external environmental orientation; green competitive advantage; green innovation; hospitality business; internal environmental orientation; South Africa